(untitled) (International journal of artificial intelligence, 2026)
This in the article future physical upbringing teachers professional competence in development gymnastics of tools pedagogical opportunities scientific in terms of analysis Research during gymnastics of tools methodical, practical - demonstrative, communicative and reflexive competencies in formation importance determined. Pedagogical experiment Bukhara state University, Asia international university and Navoi pedagogy 240 students studying at the institute student in the presence of take In the study pedagogical observation, testing, questionnaire surveys​ and mathematical-statistical analysis from the methods used. Obtained to the results according to experience​ group in students methodical competence from 21.4% to 67.8%, practical and demonstrative competence from 24.3% to 71.2%, communicative competence from 28.6% to 73.4 % and reflexive-diagnostic competence from 19.8% to 69.1 % increased was determined. Statistical analyses as a result experience group indicators control to the group at the p≤0.05 level reliable high the result record The research results gymnastics from the means systematic and methodical basically use future physical upbringing teachers professional readiness effective development confirmed.